Aklavik area centre receiving solar panels from Arctic Energy Alliance solar project -June 2016 ... - Lukasewich, Megan (University of Alberta Library, 2016)
Men hoist a solar panel to the roof of the Sittichinli Recreational Complex, Aklavik, NT. ...